EVALUASI PELAKSANAAN PILAR PERTAMA STOP BUANG AIR BESAR SEMBARANGAN PADA PROGRAM SANITASI TOTAL BERBASIS MASYARAKAT DI KABUPATEN NAGEKEO - Charles foeh Foeh; Tri Joko; Yusniar Hanani Darundiati (Jurnal Kesehatan Masyarakat, 2019)
Community-Led Total Sanitation (CLTS) is an approach to influence hygiene and sanitation behavior by triggering in the community. CLTS includes 5 pillars, Open Defecation Free (ODF), washing hands with soap, managing safe drinking water and food, securing household waste, managing household waste water safely. Within 6 years of CLTS implementation in Nagekeo District there were 18 villages that had reached the ODF (Open Defecation Free) village. This shows that there are 95 villages that have not yet reached ODF (Open Defecation Free). This study aims to evaluate the implementation of the first pillar to stop open defecation free in a community led total sanitation program in Nagekeo District which includes the stages of input, process and output. This study uses an evaluation method with a qualitative approach. The sampling technique was purposive sampling and carried out by in-depth interviews. The number of samples in this study were 7 people who managed CLTS primary health center. The study was conducted in 7 primary health center in Nagekeo District, NTT Province in May 2019. The results of this study show such a lack of quantity and quality of human resources, budget constraints, limited facilities, lack of monitoring evaluation, inactivity of village facilitator teams, lack of cross-sectoral cooperation. The conclusion of the sanitation program implementation of the first CLTS pillar, which is to stop open defecation free in Nagekeo Regency, has not been able to work properly because there are several conditions in the implementation. It is expected that assistance from the Nagekeo District Health Office in implementing the CLTS Program in the first pillar is to stop open defecation free and provide training for the CLTS facilitator team.Keywords: evaluation, clts, odfReferesnce: 42 (1996-2016)